Triggers of inland heavy rainfall inducing convective storms in West Africa : Case study of June, 2021 - G.A. Torsah; M.A. Osei; J.N.A. Aryee; J.A.A. Oti; L.K. Amekudzi (Weather and Climate Extremes)
Due to their rapidly changing atmospheric processes, forecasting thunderstorms resulting from the merger of isolated cells is a complex task for highly-resolved numerical weather prediction models. This study employed a novel approach to establish the processes that drive updrafts and downdrafts in the merger of isolated thunderstorm cells that produced heavy rainfall and flooding in Kumasi and other parts of the Ashanti Region during June 23–24, 2021. We examine the dynamic and thermodynamic factors to determine the processes that led to the heavy rainfall. The study confirms that the established moisture gradient between the south and north of the region leads to differential surface heating that deepens the planetary boundary layer. Additionally, colder air aloft a warmer surface induces atmospheric overturning, impacts the CAPE and produces substantial updrafts. Also, lower equivalent potential temperature values before storm events, coupled with reduced warming and moisture and increased vertical motion, especially in the mid-levels, favor dry air entrainment, thereby enhancing updraft potential in the mid-troposphere. Besides, the study found that strong rainfall during storms correlates with high soil moisture, evaporative fraction, and variable CAPE and updrafts, which prolonged surface convergence and upper-level divergence, leading to sustained convective activity and heavy rainfall. Notably, the study establishes the roles of African Easterly Waves and low-level wind shear in influencing thunderstorm updrafts and rainfall propagation. Furthermore, we found a single-cell thunderstorm with a variable wind pattern that impacted a defined path during the storm progression. These findings provide valuable information to enhance the development of early warning systems for the detection of localized thunderstorm activities during the monsoon period.